Resin-based sealer penetration into dentinal tubules after the use of 2% chlorhexidine gel and 17% EDTA: in vitro study - Natalia Sabadin; Daiana Elisabeth Böttcher; Carolina Bender Hoppe; Régis Burmeister dos Santos; Fabiana Soares Grecca (Universidade Estadual de Campinas, 2010)
Aim: To evaluate, by confocal laser scanning microscopy (CLSM), the influence of 17% EDTA final irrigation on the penetration of an endodontic resin-based sealer into dentinal tubules after use of 2% chlorhexidine gel. Methods: Forty extracted bovine incisors were instrumented according to the groups: G1 - root canal preparation with 2% chlorhexidine gel (n=10); G2 - root canal preparation with 2% chlorhexidine gel and final irrigation with 17% EDTA (n=10); G3 - root canal preparation with saline and final irrigation with 17% EDTA (n=10); G4 - root canal preparation with saline (n=10). The samples were filled with gutta-percha using AH Plus sealer with rhodamine B fluorescent dye. After seven days, the teeth were sectioned at the coronal, middle, and apical thirds and viewed under confocal microscope. The most representative area of penetration depth was measured in each group. Statistical significance for the sealer penetration area was determined among groups using one-way ANOVA followed by Tuckey test. For thirds comparison, in each group, data were statistically analyzed using Friedman test (p<0.05). Results: The maximum penetration was provided by G2 - 2% chlorhexidine + EDTA (p=0.000). According to this criterion, no differences were found among the other groups and among thirds within the same group. Conclusions: Based on these results, the use of 17% EDTA should be indicated after root canal preparation with 2% chlorhexidine gel for smear layer removal, enhancing the AH Plus sealer penetration.